The macroeconomic effect of fiscal policy in South Africa: A narrative analysis - Tumisang Loate; Romain Houssa; Nicola Viegi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper analyses the macroeconomic effect of legislated personal income tax changes in South Africa over the 1996-2019 period. We identify personal income tax shocks using a narrative approach and incorporate these shocks in a proxySVAR model. Our analysis shows that permanent changes in personal income taxes have a larger and significant effect on output through both the investment and consumption channels. We also find that personal tax cuts have a persistent effect on output through the investment channel in the 1996-2010 sub-sample.
Additional information: Note: On 22 November 2021, missing acknowledgements were added.
Keywords: C32; E23; E62; H24; 330; tax changes; narrative approach; proxySVAR; macroeconomic effects; South Africa